Emergency Snakebite Action Plan - Steve A. Johnson; Martin B. Main (EDIS)
In the unfortunate event that a child is bitten at school by a venomous snake, teachers and administrators should be prepared. We encourage schools to develop a plan of action and immediately initiate the plan if necessary. This document is WEC 200, one of a 4-part series of the Wildlife Ecology and Conservation Department entitled Dealing with Venomous Snakes in Florida School Yards, UF/IFAS Extension. Original publication date September 2005.